La prescripción de las acciones provenientes de actos o contratos laborales y su contravención expresa del principio constitucional de irrenunciabilidad de los derechos e intereses del trabajador. - Mora Sanmartin, Judith Alexandra (2014)
Labour law and its application are subject to the principles of social law, which is a right to protect the weakest part of the worker-employer relationship. Therefore, the labor law and social law contains rules and principles universally accepted among which the work of inalienability and inviolability. For these reasons, we have to distinguish labor law as a special law; and, therefore, deserves special study, since their rules as I mentioned tend to balance the effect of the law of economic imbalance and power of the holders of the means of production with the historically antagonistic to the working class. This research is based on the inalienable character of labor rights, considering that any stipulation to the contrary is null and void, by the statement of work indispensability of the protective principle guaranteed by the state as a means to achieve work life dignity and justice for the working class. The duty to work is a must for every individual of the human species, so that the Ecuadorian legal system states that the work is required with the limitations prescribed by law. It is thus a social obligation for any age and able to work, do so to contribute to the development of the society to which it belongs. Labour law and its application are subject to the principles of social law, which is a right to protect the weakest part of the worker-employer relationship. Therefore, the labor law and social law contains rules and principles universally accepted among which the work of inalienability and inviolability. For these reasons, we have to distinguish labor law as a special law; and, therefore, deserves special study, since their rules as I mentioned tend to balance the effect of the law of economic imbalance and power of the holders of the means of production with the historically antagonistic to the working class. This research is based on the inalienable character of labor rights, considering that any stipulation to the contrary is null and void, by the statement of work indispensability of the protective principle guaranteed by the state as a means to achieve work life dignity and justice for the working class. The present study evaluated a legal problem of deep social resonance, currently the application of the legal concept of prescription from acts or labor contracts has limited the exercise of representation of workers as intended to sue the repair of a right infringed or violated. Regarding the issue, I give a broad theoretical and doctrinal content specifically related to the labor principles of inalienability and inviolability labor. Finally I emphasize the need to incorporate a legal reform stating as imprescriptible actions arising from acts or labor contracts, this work is borne out by conducting a field study regarding the problem to investigate, to what has been collected the criterion of a set of officials and judicial officers who have expressed their views and opinions regarding the proposed theme. The study with the development of the respective casuistry, conclusions, recommendations, and the proposed legal reform is complemented. Regarding the issue, I give a broad theoretical and doctrinal content specifically related to the labor principles of inalienability and inviolability labor. Finally I emphasize the need to incorporate a legal reform stating as imprescriptible actions arising from acts or labor contracts, this work is borne out by conducting a field study regarding the problem to investigate, to what has been collected the criterion of a set of officials and judicial officers who have expressed their views and opinions regarding the proposed theme. The study with the development of the respective casuistry, conclusions, recommendations, and the proposed legal reform is complemented.